Traditional agro-management practices, utilization and nutritional composition of momala: A local maize variety of Gorontalo, Indonesia - NOVRI YOULA KANDOWANGKO; MARGARETHA SOLANG; ERNA RETNAWATY (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kandowangko NY, Solang M, Retnawaty E. 2020. Traditional agro-management practices, utilization and nutritional composition of Momola-a local maize variety of Gorontalo, Indonesia. Biodiversitas 21: 853-859. Maize (Zea mays, L.) or corn, locally called milu or binthe (Gorontalo language), has been a popular crop among Gorontalo people for a long time. People mostly use baby corn as the main ingredient of binthe biluhuta, famous traditional food in Gorontalo. momala is a local maize variety of Gorontalo the cultivation of which is decreasing. The cause is a shift in farmers’ preference of the crop, most of them preferring hybrid variety over momala. Decrease in cultivating local maize has also led to a decline in the local farmers’ traditional knowledge of the crop. Therefore, initiatives to raise awareness of the importance of cultivating local crops are essential for their popularization and conservation purposes. This research is aimed at (i) exploring the traditional knowledge of local farmers pertaining to agro-management of maize or corn, (ii) describing the utilization of momala, and (iii) investigating the nutritional composition of momala, both by qualitative and quantitative methods The results revealed that the corn farmers apply the principle of huyula or gotong royong (communal work) in their agriculture activities. The people are using momala corn as the main ingredient of local food preparations, such as binthe biluhuta (clear corn soup), balobinthe (corn rice), and kokole (soft, pudding-like corn cake), in addition to some traditional rituals. Nutritional analysis indicated that its ash content is 1.34-2.86%, crude protein is 9.09-11.67% crude fat is 4.29-4.96%, and carbohydrate is 67.68-68.16%. Furthermore, the composition of nitrogen-free extract ranges from 57.85-72.96% and metabolic energy content ranges from 2896.94-3352.77 Kcal/kg. Measures to conserve and improve momala are necessary to promote food security of people.